APOE Variants E2, E3, and E4 Can Be Miscalled By Classical PCR‐RFLP When The Christchurch Variant Is Also Present. Issue 2 (27th August 2016) - Candás‐Estébanez, Beatriz; Padró‐Miquel, Ariadna; Ruiz‐Iruela, Cristina; Corbella‐Inglés, Emili; Pintó‐Sala, Xavier; Alía‐Ramos, Pedro
Abstract : Background: The APOE Christchurch ( APOECh ) is a rare variant (c.543C>A) in codon 154. It was first described in an E2 patient with type III dyslipidemia, and thus initially called E2 Ch. Its prevalence and the lipid profile of carriers remain unclear. Methods: E2, E3, and E4 screening for the APOE gene was performed by PCR‐RFLP. The rare APOE Ch variant was firstly found after detecting an unexpected 109 base‐pair band in the high‐resolution agarose gel electrophoresis leading to a genotype misinterpretation: the presence of APOE Ch alters the restriction‐bands pattern. To confirm the Ch variant, a second PCR‐RFLP method was specifically designed to detect this variant and Sanger sequencing was also performed for all positive samples. Results: We identified 12 unrelated subjects for the APOECh among a cohort of 2, 560 patients: nine E3/E3Ch, two E3Ch/E4, and one E2/E3Ch or E2Ch/E3. The frequency of the variant is 0.4% in our study population, which represents the highest percentage published so far. If there is a 109 bp band, it is easy to recognize the presence of the variant. However, in APOE routine genotyping, an E4Ch allele is indistinguishable from a standard E3. Therefore, E4Ch alleles might be underrepresented in the results. Conclusion: We recommend APOE exon 4 sequencing to unequivocally detect the common three variants E2, E3, and E4 and the rare variants as well, to find out the real role they play in atherosclerosis and to estimate its real frequency which is nowadays unclear, in part by the small number of cases identified.